Myeloid Dendritic Cells are Potential Players in Human Neurodegenerative Diseases - Bossù, Paola; Spalletta, Gianfranco; Caltagirone, Carlo; Ciaramella, Antonio (Frontiers in Immunology, 2015)
Alzheimer’s diseases (AD) and Parkinson’s diseases (PD) are devastating neurodegenerative disturbances, wherein neuroinflammation is a chronic pathogenic process with high therapeutic potential. Major mediators of AD/PD neuroimmune processes are resident immune cells, but immune cells derived from periphery may also participate and to some extent modify neuroinflammation. Specifically, blood borne myeloid cells emerge as crucial components of AD/PD progression and susceptibility. Among these, dendritic cells (DCs) are key immune orchestrators and players of brain immune surveillance; we candidate them as potential mediators of both AD and PD and as relevant cell model for unraveling myeloid cell role in neurodegeneration. Hence, we recapitulate and discuss emerging data suggesting that blood-derived DCs play a role in experimental and human neurodegenerative diseases. In humans, in particular, DCs are modified by in vitro culture with neurodegeneration-associated pathogenic factors and dysregulated in AD patients, while the levels of DC precursors are decreased in AD and PD patients’ blood, possibly as an index of their recruitment to the brain. Overall, we emphasize the need to explore the impact of DCs on neurodegeneration to uncover peripheral immune mechanisms of pathogenic importance, recognize potential biomarkers, and improve therapeutic approaches for neurodegenerative diseases.